Managing trypanosomosis: knowledge, attitude and practice in Upper Guinea - Grace, Delia (International Livestock Research Institute, 2004)
This study was carried out in Northeast Guinea to investigate farmer knowledge, attitude and practice (KAP) relating to trypanosomosis management; elucidate factors that influence animal-health-seeking behaviour and outcome; and investigate factors associated with high risk for chemo-resistance. It describes how farmers manage trypanosomosis in Mandiana Prefecture, Upper Guinea; identifies problems in management leading to inadequate disease control or drug resistance; investigates the variables which influence health-seeking behaviour and health outcomes as well as the variables associated with risk of resistance to trypanocides; and suggests strategies for improving the management of trypanosomosis and trypanocide resistance. Questionnaires were administered to farmers (no. = 300) and animal health service providers (AHSP) (no. = 16) and Rapid Assessment Procedures (RAP) used to obtain qualitative data.